2015
DOI: 10.1111/jfpp.12497
|View full text |Cite
|
Sign up to set email alerts
|

Effect by Gamma Irradiation and Low-Temperature Storage on Bacteriological Profile of Edible Estuarine CrabScylla serrata

Abstract: The effect of dose-dependent gamma irradiation and subsequent cold storage on bacteriological profile of tissues derived from Scylla serrata was evaluated. Irradiation at 0.5, 1.0 and 2.0 kGy significantly reduced the (P = 0.0001) total plate count (TPC) by 1.0, 2.0 and 2.5 log units, respectively. Treatments of 1.0 and 2.0 kGy irradiation reduced total coliform (TC) count below 1 most probable number (MPN)/g in the muscle and hepatopancreas and below 50 MPN/g in the gills of S. serrata. Irradiated tissues sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…It was found that microbial loads were below the limits (6 log CFU/g) during 9 weeks of storage (2 ± 1 °C). Arshad, Sudha, Hatha, and Anilkumar () investigated the synergistic effect of cold temperature storage and gamma‐irradiation on the sensory properties of estuarine crab ( Scylla serrate ) and reported that frozen storage (−20 °C) and cold (4 °C) and gamma‐irradiation (1.0 to 2.0 kGy) extended the shelf‐life of the sample by maintaining sensory quality for the maximum duration of 28 and 14 days, respectively.…”
Section: Irradiationmentioning
confidence: 99%
“…It was found that microbial loads were below the limits (6 log CFU/g) during 9 weeks of storage (2 ± 1 °C). Arshad, Sudha, Hatha, and Anilkumar () investigated the synergistic effect of cold temperature storage and gamma‐irradiation on the sensory properties of estuarine crab ( Scylla serrate ) and reported that frozen storage (−20 °C) and cold (4 °C) and gamma‐irradiation (1.0 to 2.0 kGy) extended the shelf‐life of the sample by maintaining sensory quality for the maximum duration of 28 and 14 days, respectively.…”
Section: Irradiationmentioning
confidence: 99%
“…The total number of aerobic bacterial colonies was determined by being poured onto plate count agar (Tryptone glucose yeast extract agar) and then incubated at (36 6 1) 8C for (48 6 2) hr (Koide & Nonami, 2007). Lauryl sulfate tryptose was used to enumerate coliforms (Arshad et al, 2015). Each test was replicated three times.…”
Section: Microbial Enumerationmentioning
confidence: 99%